Annexin‐A2 as predictor biomarker of recurrent disease in endometrial cancer. Issue 8 (29th September 2014) - Alonso‐Alconada, Lorena; Santacana, Maria; Garcia‐Sanz, Pablo; Muinelo‐Romay, Laura; Colas, Eva; Mirantes, Cristina; Monge, Marta; Cueva, Juan; Oliva, Esther; Soslow, Robert A; Lopez, Maria Angeles; Palacios, Jose; et al.
<x xml:space="preserve">Abstract</x> Endometrial carcinomas, the most common malignant tumour of the female genital tract, are usually diagnosed at an early stage with uterine‐confined disease and an overall favourable prognosis. However, up to 20% of endometrial carcinomas will end up in recurrent disease, associated with a drop in survival and representing the major clinical challenge. Management of this group of risk patients relies on robust biomarkers that may predict which endometrial carcinomas will relapse. For this, we performed a proteomic analysis comparing primary lesions with recurrences and identified ANXA2 as a potential biomarker associated with recurrent disease that we further validated in an independent series of samples by immunohistochemistry. We demonstrated in vitro a role for ANXA2 in the promotion of metastasis rather than interfering with sensitivity to radio/chemotherapy. In addition, ANXA2 silencing resulted in a reduced metastatic pattern in a mice model of endometrial cancer dissemination, with a limited presence of circulating tumor cells. Finally, a retrospective study in a cohort of 93 patients showed that ANXA2 effectively predicted those endometrioid endometrial carcinomas that finally recurred. Importantly, ANXA2 demonstrated a predictive value also among low risk Stage I endometrioid endometrial carcinomas, highlighting the clinical utility of ANXA2 biomarker as predictor of recurrent disease in endometrial cancer. Retrospective and prospective studies are ongoing to validate ANXA2 as a potential tool for optimal stratification of patients susceptible to receive radical surgery and radio/chemotherapy.